Establishing environment sustentation strategies for urban and rural/town tourism based on a hybrid MCDM approach. Issue 19 (1st October 2020) - Lin, Chia-Li
ABSTRACT: The initial views of community empowerment were considered residents as the subject for construction in the city and town. Because the development of city and town also increased tourism, in recent years residents have been encouraged to remodel with new styles and features. This study tries to explore the driving forces for the development of urban and rural/town tourism. The findings will allow stakeholders (residents, tourists, sojourners, and government) to reexamine the future for the development of urban and rural tourism and to rediscover new value-driving forces by the urban and rural/town tourism development. This study defines an evaluation system of urban and rural tourism by four aspects: cultural preservation, environment sustentation, economic development, and social consciousness. This study adopts the integrated MCDM approach to evaluate the SDI (Sustainable Development Index) for urban and rural/town tourism based on the five tourist towns in northern Taiwan. The research findings will help authorities understand the competitive advantages of tourism in each location and draw up development strategies for urban and rural/town tourism based on the common value of stakeholders. This study also proposes new viewpoints and tourist highlights to help stakeholders identify the next generation for tourism in urban and rural areas.